Lymphokines : a forum for immunoregulatory cell products. - Pick, Edgar; Landy, Maurice (Academic Press, 1987)
Lymphokines: A Forum for Immunoregulatory Cell Products, Volume 14, reviews the state of knowledge on lymphokines. The book opens with an integrative view of the role of lymphokines in the generation of fever. It stresses that pirogenicity is the attribute of more than one lymphokine: interleukin 1 (IL-1), interferon a, and tumor necrosis factor (TNF) all possess this quality. This is followed by separate chapters on the chemistry of IL-1 molecules and cloning of the gene for human monocyte IL-1; the production of lymphokine by cells of the central nervous system; the acute phase plasma prote.